Bridging Tradition and Modernity: The Dynamics of Classical and Contemporary Literature for Students - Sahrudin Sahrudin; Wakib Kurniawan; Supriyatmoko Supriyatmoko (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the dynamics of adab from both classical and contemporary perspectives and to formulate an integrative model capable of bridging tradition and modernity within the context of student education. The study employs a qualitative approach using a library research design combined with conceptual analysis. Data were obtained from various relevant primary and secondary literature sources and analyzed using content analysis and thematic analysis through stages of reduction, categorization, comparison, and synthesis. The findings indicate that, from a classical perspective, adab serves as the primary foundation of education, integrating intellectual, moral, and spiritual dimensions in a holistic manner. However, in contemporary contexts, there has been a shift in educational orientation that tends to prioritize cognitive aspects and technical competencies, resulting in the reduction of adab to merely formal ethics. In addition, the development of digital technology has influenced the dynamics of adab value internalization among students. In response to these conditions, this study proposes an integrative model of adab that emphasizes value reintegration, contextualization within modern life, a student-centered learning approach, and pedagogical transformation based on role modeling and reflection. This model is expected to serve as a conceptual foundation for developing education that is not only oriented toward intellectual competence but also toward the formation of students’ character and moral integrity. This study contributes theoretically to the development of a more contextual and integrative concept of adab, as well as practically to strengthening character education in the modern era.